2021
DOI: 10.1167/iovs.62.15.7
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Ambient Air Pollution With Cataract Surgery in UK Biobank Participants: Prospective Cohort Study

Abstract: Purpose Air pollution is associated with chronic diseases of later life. Cataract is the most common cause of blindess globally. It is biologically plausible that cataract risk is increased by pollution exposure. Therefore, the relationship between air pollution and incident cataract surgery was examined. Methods This was a prospective, observational study involving 433,727 UK Biobank participants. Ambient air pollution measures included particulates, nitrogen dioxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In order to estimate ground-level concentrations of multiple air pollutants such as PM 2.5 , sulfur dioxide (SO 2 ), ozone (O 3 ), and NO 2 based on the municipality, a hybrid kriging/LUR model was used, and the results indicated female exposure to high levels of NO 2 had significantly increased risk of dry eye syndrome ( 24 ). In a recent prospective, observational study to examine the relationship between ambient air pollution exposure and incident cataract surgery in the UK, those outdoor air pollution included particulates, NO 2 , and nitrogen oxides (NO x ) was estimated based on LUR models developed by the European Study of Cohorts for Air Pollution Effects (ESCAPE) project ( 36 ), and their impacts on the risk of future cataract surgery were increased ( 25 ).…”
Section: Application In Ophthalmologymentioning
confidence: 99%
“…In order to estimate ground-level concentrations of multiple air pollutants such as PM 2.5 , sulfur dioxide (SO 2 ), ozone (O 3 ), and NO 2 based on the municipality, a hybrid kriging/LUR model was used, and the results indicated female exposure to high levels of NO 2 had significantly increased risk of dry eye syndrome ( 24 ). In a recent prospective, observational study to examine the relationship between ambient air pollution exposure and incident cataract surgery in the UK, those outdoor air pollution included particulates, NO 2 , and nitrogen oxides (NO x ) was estimated based on LUR models developed by the European Study of Cohorts for Air Pollution Effects (ESCAPE) project ( 36 ), and their impacts on the risk of future cataract surgery were increased ( 25 ).…”
Section: Application In Ophthalmologymentioning
confidence: 99%
“…Recently, the effect of PM 2.5 on age-related cataracts was noted by researchers, ,, but the results were inconsistent, and only the study by Chua et al . showed that exposure to PM 2.5 was associated with a significantly increased risk of cataracts, which may be due to study design and small sample size limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In China, blindness caused by cataracts accounts for 33.92% of blind people . As a result of the population aging, age-related cataracts have been a substantial disease and social burden. , The risk of cataracts depends on a variety of factors, such as unhealthy lifestyle factors, genetics, age, and environmental pollution. With the rapid development of industrialization, growing evidence suggests that air pollution could have an important role in the risk of cataracts. ,, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations